Crescimento econômico e desigualdade de oportunidades : uma análise para os estados brasileiros - Rosa, Thais Santana da (2016)
This study investigated the effect of income inequality on economic growth in Brazil, decomposing it into two elements: the inequality of opportunity and effort. To calculate the inequality of opportunity we used a methodology developed by Barros et al. (2009). The analysis occurs at the state level for the period 1998 to 2013. It was used also as independent variables: GDP per capita lagged annual, inequality of opportunity, inequality of effort, the proportion of the adult population of men and women who completed at least one year of secondary education, the interaction dummies for sectors of the economy, the ratio between revenues and GDP and expenditure and GDP. The empirical strategy was to estimate the model for the rate of economic growth through four econometric techniques: OLS, effects-Series, difference-GMM and system-GMM. The results showed the negative impact of inequality of opportunity and effort on economic growth. Also, found a more negative impact of inequality of opportunity for growth, given low levels of GDP per capita through variable interaction. The ratio of public spending to GDP showed that a larger income inequality tends to make biased government decisions in favor of redistribution income and at the expense of economic growth.